Effective two Higgs doublets in nonminimal supersymmetric models - Ma, Ernest; Maniatis, Markos (The European physical journal. C, Particles and fields, 2011)
The Higgs sectors of supersymmetric extensions of the Standard Model have two doublets in the minimal version (MSSM), and two doublets plus a singlet in two others: with (UMSSM) and without (NMSSM) an extra U(1)′. A very concise comparison of these three models is possible if we assume that the singlet has a somewhat larger breaking scale compared to the electroweak scale. In that case, the UMSSM and the NMSSM become effectively two-Higgs-doublet models (THDM), like the MSSM. In this approach the well-known upper mass bounds on the lightest CP-even neutral Higgs boson can be derived in a very simple and transparent way.
Gesehen am 22.11.2022